2010
DOI: 10.5370/jeet.2010.5.2.342
|View full text |Cite
|
Sign up to set email alerts
|

The Development of an Electroconductive SiC-ZrB2Composite through Spark Plasma Sintering under Argon Atmosphere

Abstract: -The SiC-ZrB 2 composites were fabricated by combining 30, 35, 40, 45 and 50 vol. % of zirconium diboride (ZrB 2 ) powders with silicon carbide (SiC) matrix. The SiC-ZrB 2 composites and the sintered compacts were produced through spark plasma sintering (SPS) under argon atmosphere, and its physical, electrical, and mechanical properties were examined. Also, the thermal image analysis of the SiC-ZrB 2 composites was examined. Reactions between β-SiC and ZrB 2 were not observed via x-ray diffraction (XRD) analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The material considered in this study is a ceramic composite consisting of SiC and ZrB 2 . Previous studies have reported that the SPS‐processed SiC–ZrB 2 ceramic composites possess high flexural strength (~1 GPa) and good electrical resistivity (~10 −3 Ω·cm) at room temperature . At elevated temperatures, this kind of composite also exhibits an excellent flexural strength .…”
Section: Annular Shape Components For Sps Tooling Applicationsmentioning
confidence: 97%
See 1 more Smart Citation
“…The material considered in this study is a ceramic composite consisting of SiC and ZrB 2 . Previous studies have reported that the SPS‐processed SiC–ZrB 2 ceramic composites possess high flexural strength (~1 GPa) and good electrical resistivity (~10 −3 Ω·cm) at room temperature . At elevated temperatures, this kind of composite also exhibits an excellent flexural strength .…”
Section: Annular Shape Components For Sps Tooling Applicationsmentioning
confidence: 97%
“…SiC powder (99.9% pure, <1 μm, Materion Advanced Material Group, Milwaukee, WI, USA) and ZrB 2 powder (99.5% pure, −325 mesh; Materion Advanced Material Group, Milwaukee, WI, USA) were utilized as starting materials. The volume percentage of ZrB 2 in the target powder composite was set to 40% as it has been reported by Lee et al, to be the optimal ratio. The mixed SiC and ZrB 2 powders were ball‐milled for 8 hours at 60 RPM to homogenize the particle distribution.…”
Section: Annular Shape Components For Sps Tooling Applicationsmentioning
confidence: 99%
“…He stated that the overriding capability of a process should include not only the production of efficiency but should also comply with the target value. Any deviation from the target results in a loss of quality and a decrease in customer satisfaction [ 47 ].…”
Section: Optimization Of Sintering Parameters During the Manufacture ...mentioning
confidence: 99%
“…However, the addition of SiC to ZrB 2 results in the formation of a SiC-ZrB 2 composite with high electrical conductivity, superior oxidation resistance, and high mechanical strength. These properties make SiC-ZrB 2 composites suitable conductive materials and Ohmic-contact electrode materials, able to function satisfactorily at both high and low temperatures [5][6][7].…”
Section: Introductionmentioning
confidence: 99%